2022
DOI: 10.1371/journal.pone.0263141
|View full text |Cite
|
Sign up to set email alerts
|

Bio-fabrication of stem-cell-incorporated corneal epithelial and stromal equivalents from silk fibroin and gelatin-based biomaterial for canine corneal regeneration

Abstract: Corneal grafts are the imperative clinical treatment for canine corneal blindness. To serve the growing demand, this study aimed to generate tissue-engineered canine cornea in part of the corneal epithelium and underlying stroma based on canine limbal epithelial stem cells (cLESCs) seeded silk fibroin/gelatin (SF/G) film and canine corneal stromal stem cells (cCSSCs) seeded SF/G scaffold, respectively. Both cell types were successfully isolated by collagenase I. SF/G corneal films and stromal scaffolds served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…facilitated by the RGD motifs in gelatin, which resembled integrin mediated cell attachment. 16,48,49 It is worth to mention that although AV has shown to enhance cell attachment due to the ability of glucomannan to bind on b2-integrins, we did not observe any differences between G and GA hydro-films 16 Anti-inflammatory study. To determine the anti-inflammatory activity of the hydro-films, we followed the experimental design represented in Fig.…”
Section: Hemolysis Assay In Vitromentioning
confidence: 64%
“…facilitated by the RGD motifs in gelatin, which resembled integrin mediated cell attachment. 16,48,49 It is worth to mention that although AV has shown to enhance cell attachment due to the ability of glucomannan to bind on b2-integrins, we did not observe any differences between G and GA hydro-films 16 Anti-inflammatory study. To determine the anti-inflammatory activity of the hydro-films, we followed the experimental design represented in Fig.…”
Section: Hemolysis Assay In Vitromentioning
confidence: 64%
“…Studies revealed endogenous ECM production after 14 days, thus mimicking native cornea. [16]. Pitarresi and coworkers were the first ones to use hydrogels based on hyaluronic acid (HA) cross-linked with polyaspartamide derivative (PHEA-EDA) as an alternative to amniotic membrane for the delivery of limbal stem cells (LSCs).…”
Section: Cell-based Therapiesmentioning
confidence: 99%